Multivariate Joint Probability Distributions for Seismic Design Parameters Across Multiple Building Codes - Yanez-Cart, S (Springer Science and Business Media B.V., 2023)
In order to contribute to the lack of statistical anomaly detection and sensitivity visualization of the response parameters from international seismic codes, this study presents a comparative analysis between multiple Chilean codes for the seismic design of reinforced concrete buildings. The seismic response and its similar implications to the US codes are studied from a model of a reinforced concrete building in the city of Viña del Mar, Chile. The first study case is the NCh433 Of.96 Mod.2009, the second case is the NCh433 Of.96 Mod.2009 + D.S. 117 and 118, and the third case is the NCh433 Of.96 Mod.2009 + D.S. 60 and 61. The results show that the seismic response does not present great differences, but they show noticeable dependencies between multiple parameters within the three study cases. The third case presents the most oversized values of the response parameters, which require a design against a higher base shear. An analysis of the bio-seismic profile is included, which is a procedure commonly used for buildings in Chile, and its indexes are analyzed with statistical models that provide an easy overview of the data structure. Additionally, a pier wall with an opening, and a pier with a T-shaped wall are selected, which present an increase in the amount of reinforcing steel from the first code case to the third, and then to the second code case. © 2023, Springer Nature B.V.